Serious Adverse Events Associated with Readmission Through One Year After Vertebral Augmentation with Either a Polyetheretherketone Implant or Balloon Kyphoplasty - Beall, Douglas P; Coe, Jeffrey D; McIlduff, Mark; Bloch, Daniel; Hornberger, John; Warner, Christopher; Tutton, Sean (Pain physician, 2017)
The KAST (Kiva Safety and Efficacy) investigation device exempt (IDE) study indicated that the majority of patients responded equally well to vertebral augmentation using either an implant-based approach or balloon kyphoplasty (BK). Additional investigation has suggested that a subset of patients may benefit further by avoiding repeated readmissions due to serious adverse events (SAEs) if they receive one vertebral augmentation approach over another. The primary aim was to assess the effect of 2 different augmentation procedures on readmission rates for SAEs. The KAST trial is a pivotal, multicenter, randomized, controlled trial conducted to evaluate an implant-based vertebral augmentation approach (implant) against BK. Post-hoc analysis was performed to evaluate SAEs and readmission rates. Twenty-one sites in North America and Europe. The treatment effect of vertebral implant versus BK on SAEs requiring unplanned readmission was evaluated by estimating the risk of SAEs associated with readmissions in KAST while controlling for key baseline covariates using multivariate Poisson regression modeling. Forty (27.8%) patients with implants had 69 SAEs associated with readmission compared to 44 (31.2%) patients with BK having 103 events. The risk for all SAEs leading to readmission was 34.4% lower with the implant than for BK (95% confidence interval = 11.1%, 51.7%; P < 0.01). Multivariate analysis showed that the risk of SAEs associated with readmission was decreased in subjects treated with the implant compared to BK, and increased in patients with prior histories of vertebral compression fractures (VCFs) or significant osteoporosis. The power of the KIVA study was based on clinical efficacy criteria to meet FDA requirements and recommendations for equivalency or noninferiority. The primary endpoint in this post-hoc analysis is SAEs associated with readmissions; as a result, the sample size is underpowered, although the results remain significant. The augmentation approaches compared here have similar pain relief and quality of life effects; the implant showed a lower risk of readmissions. ClinicalTrials.gov Identifier: NCT01123512. Key words: Vertebral compression fracture, kiva implant, balloon kyphoplasty, vertebroplasty, health economics, osteoporosis.